Pemberdayaan Kelompok Tani melalui Workshop Pembuatan Pupuk Kompos dari Limbah Bonggol dan Pelepah Pisang untuk Mendukung Kemandirian Pupuk Pertanian Pisang - Qomaliyah, Eka Nurul; Arista, Rini Anggi; Nugraheni, Dian; Riyanto, Obaja Eden Santosa; Arifin, Achmad Saiful; Praptawati, Atika (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Ngrangin Hamnlet, Sumberpasir Village, Malang Regency, is a major banana growing area that produces a lot of organic waste from banana stems. Sadly, this waste is not being used as well as it could be, even though there is a growing need for fertilizer, which is often hard to get for farming. The Purpose of this community service is to help banana farmers learn how to make compost from banana plant waste. This will help them become more self-sufficient effective in getting organic fertilizer locally. This workshop used a learning and hands on approach, including advice, practice and technical help. The activity was aimed at 26 banana farmers who belong to farmer group in Ngrangin Hamlet. The result show that the farmer understood more about recycling farm waste and had better skills in making compost. The compost was good quality, with a crumby texture, dark brown colour, and odorless. Another good thing was that banana farmer started working together to manage compost in the hamlet and they became more aware of sustainable farming methods. This activity shows that helping people locally with the right technology can be a good way to manage waste and provide the fertilizer farmers need.